A Comprehensive Literature Review of Fournier's Gangrene in Females - Khalid, Aisha; Devakumar, Sahana; Huespe, Ivan; Kashyap, Rahul; Chisti, Imran (Curēus (Palo Alto, CA), 2023)
Fournier gangrene (FG) is a rare but rapidly progressing disease with a higher mortality rate in women as compared to men. This study aims to perform a literature review about FG in females and associated mortality and morbidity. We searched databases including MEDLINE (Ovid), the National Library of Medicine (Medical Subject Headings (MeSH)), the Cochrane Database of Systematic Reviews (Wiley), as well as Embase (Ovid), Scopus, and Global Index Medicus (WHO), and reviewed literature from 2002 to 2022 and selected 22 studies that met our study's inclusion criteria, which included 134 female patients with a mean age of 55±6 years. The perineal abscess was a more common nidus (n=41, 35%; 95%CI 23-39%) than vulvar pathology (n=29, 22%; 95%CI 15-30%). The most common initial presentation was cellulitis (n=62, 46%; 95%CI 38-55%), followed by perineal pain (n=54, 40%; 95%CI 32-50%), fever (n=47, 35%; 95%CI 27-43%), and septic shock (n=38, 28%; 95%CI 21-37%). was the most frequently identified bacteria (n=48, 36%; 95%CI 28-46%). All patients had treatment with a mean of three (SD 2) debridement and those with negative pressure dressings received fewer debridements than those who received a conventional dressing. However, of those who had surgical intervention, 28 (20%; 95%CI 14-29%) patients underwent diversion colostomy. General surgeons performed 78% (n=104) of cases out of which 20% (n=20) were consulted by obstetrician-gynecologists, 14% (n=18) were treated by urologists, and only 8% (n=10) by plastic surgeons. The mean length of stay in the hospital was 24±11 days, and the gross mortality rate was 27 (20%; 95%CI 14-28%). In conclusion, while females have a low incidence rate of FG, they carry a higher mortality rate. Lack of cardinal signs and delayed presentation to the hospital from the onset of symptoms are some possible causes for the increased mortality rate along with the disease process being under-recognized in women. A high index of clinical suspicion is essential to avoid delay in the definitive management coupled with an early surgical consult and establishing a common general care pathway could minimize mortality and morbidity.